Phytonutrients Composition of Nigerian Banana Fruits (Musa species) And Their Peel Extracts - John Isa, Justinah Folasade (International Journal of Human and Health Sciences (IJHHS), 2024)
Objective: The aim of this study is to determine the phytonutrients components of banana fruits and that of their peel extracts. Methods: Two (2) banana fruit types; Yoruba (local) and Igbo banana and their peel extracts were evaluated in this research Results: The two banana types revealed the presence of some bioactive compounds such as like phenols, alkaloids, flavonoids, glycoside, terpenoid, tannin, saponin, carotenoids, potassium, sodium and fibre at varying concentrations. The phytonutrients analysis of the banana fruits samples showed that Alkaloids had a mean range between 0.17±0.002 and 0.18±0.001mm. Phenolic contents with the mean values ranging from 1.57±0.01 to 1.70±0.01mm. Carotenoid had a mean range between 3.79±0.003 and 5.01±0.01mm. There was no significance difference in the Flavonoids contents with the mean values 0.09±0.00 to 0.09±0.001mm. Potassium contents mean values of the two banana fruits samples ranged from 165.5±0.71 to 175.00±2.83mm, Sodium contents of the banana fruits samples ranged from 122.00±0.00 to 117.00±1.41mm and Fibre contents ranged from 0.01±0.001 to 0.02±0.002mm. The phytonutrients analysis of the banana peel extract showed the presence of glycoside, terpenoid, alkaloids, flavonoids, tannin and saponins. The presence of these phytonutrients confirms the two Musa species tested to be of medicinal value. The extract of the two selected banana peels showed various inhibitory effect against selected microbial isolates. The results of this study revealed that Yoruba (local) banana peel extracts has the highest zone of inhibition (26.50±3.61mm) on Staphylococcus aureus compared to Igbo banana peel extracts (20.33±2.47mm). However, Igbo banana peel extract (18.33±1.61mm) showed a little higher growth inhibition on Escherichia coli compared to Yoruba (local) banana peel extract (17.43±1.68mm). Conclusion: The presence of these bioactive compounds in banana fruits and their peel showed a positive role in maintaining immune function in the body system. International Journal of Human and Health Sciences Vol. 08 No. 02 Apr’24 Page: 170-176